Joy Bauer's food cures : eat right to get healthier, look younger, and add years to your life - Bauer, Joy.; Svec, Carol (New York : Rodale Books : Distributed to the trade by Macmillan, 2011)
"In 2007, New York Times bestseller Joy Bauer's Food Cures taught readers what and how they should eat to achieve optimal health. Now, in a brand new, fully revised edition, Joy brings readers up to date on the most current science and research regarding nutrition and diet , presenting to-the-minute information on the specific foods and nutrients we need to boost metabolism and lose weight, treat skin and beauty issues, and prevent a whole range of health problems and diseases. Included are quick and easy recipes, shopping lists updated with all of today's available food products, current exercise and supplement recommendations, and the inside scoop on our nation's hottest nutritional topics. Comprehensive, accessible, and totally fresh, Joy Bauer's Food Cures, Revised Edition will replace the original as every reader's guide to thinking like a nutritionist--and achieving their best health possible"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Diet therapy -- Popular works